MENERA ULANG KAJIAN KEBUDAYAAN MATERIAL MODERN DALAM ARKEOLOGI - Nur Ihsan D. (Balai Arkeologi Provinsi Sulawesi Selatan, 2009)
The Ontological aspect of archaeology is its attention on ancient material culture that is utilized as a basis in interpretating the past of human's culture. Along with science development, there's a rising effort to evaluate that ontological aspect by redefining archaeology becomes the science that studing human interaction relationship with its material culture regardless time and space. That redefinition affects the rise of Modern Material Culture in Archaeology. But, its stagnant implementaion and the development of other scince that also begins to paying attention on the significant of material dimention of the culture constitutes a challenge in developing modern material culture in archaeology. Even so, the emergence of this new field study is belived as a new direction in the development archaeology.Aspek ontologis dari arkeologi adalah perhatiannya pada budaya material kuno yang digunakan sebagai dasar dalam menafsirkan masa lalu budaya manusia. Seiring dengan perkembangan sains, ada upaya yang meningkat untuk mengevaluasi aspek ontologis dengan mendefinisikan kembali arkeologi menjadi ilmu yang mempelajari hubungan interaksi manusia dengan budaya materialnya terlepas dari ruang dan waktu. Redefinisi itu mempengaruhi bangkitnya Budaya Material Modern dalam Arkeologi. Namun, implementasinya yang stagnan dan pengembangan ilmu lain yang juga mulai memperhatikan signifikansi dimensi material budaya merupakan tantangan dalam mengembangkan budaya material modern dalam arkeologi. Meski begitu, kemunculan studi lapangan baru ini diyakini sebagai arah baru dalam pengembangan arkeologi.